Climate Change Scepticism : A Form of Fundamentalist Belief? - Kalicharan Veera Singam (2018)
The scepticism over climate change persists although adverse effects from a warming planet are already being felt. Is such scepticism, predicated upon belief, a form of fundamentalism?